2015
DOI: 10.1111/cen.12711
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation and testosterone concentrations in male human subjects

Abstract: In this post hoc analysis of three small clinical trials of limited duration in men with normal baseline testosterone concentrations, vitamin D supplementation was not associated with an increase in circulating testosterone concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 33 publications
(64 reference statements)
3
45
2
1
Order By: Relevance
“…The reasons for fall in serum testosterone after 6 months are not clear, especially when the earlier RCT and observational study in young and older males showed increase in serum testosterone after vitamin D supplementation . Two recent RCTs assessing the effect of vitamin D supplementation on serum testosterone reported no significant effect of vitamin D supplementation on serum testosterone in young males . Thus, three of the 4 RCTs including the present study show no significant effect of cholecalciferol supplementation on serum testosterone.…”
Section: Discussioncontrasting
confidence: 62%
“…The reasons for fall in serum testosterone after 6 months are not clear, especially when the earlier RCT and observational study in young and older males showed increase in serum testosterone after vitamin D supplementation . Two recent RCTs assessing the effect of vitamin D supplementation on serum testosterone reported no significant effect of vitamin D supplementation on serum testosterone in young males . Thus, three of the 4 RCTs including the present study show no significant effect of cholecalciferol supplementation on serum testosterone.…”
Section: Discussioncontrasting
confidence: 62%
“…52,55 Indeed, 25-(OH)D has been significantly and positively associated with total testosterone and SHBG levels before and after adjustment for age and ethnicity, 56 although VitD supplementation per se does not appear to influence testosterone levels. 57 In addition, short-term administration of testosterone does not appear to alter 25-(OH)D levels. 58 The most intriguing finding of our study was the suboptimal 25-(OH)D values observed in both genders (males=19.48±9.51 and females=18.01±9.01, ng/ mL±SD), contrary to what would be expected in an area with abundant sunshine and a population prone to outdoor activities.…”
Section: Discussionmentioning
confidence: 96%
“…Later studies among healthy European men confirmed this tendency by showing that lower levels of vitamin D were significantly correlated with lower total and free testosterone amounts (Lee et al ., ). However, after supplementing subjects with vitamin D, the increase of amount of testosterone was not statistically significant (Heijboer et al ., ). On the contrary, a study of men in China did not find correlations between 25(OH)D and testosterone levels (Yang et al ., ).…”
Section: Discussionmentioning
confidence: 97%